Empirical Study of the Dinamics Contribution of Public Communication Based on Local Wisdom to Development - Andi Windah; Haryanto Hasan; Tina Kartika; Ida Nurhaida (LONTAR: Jurnal Ilmu Komunikasi, 2022)
Communication is one of the crucial indicators in development, especially to build consensus and facilitate knowledge sharing to achieve positive change in development initiatives. One form of development communication that emphasizes the ability of communicators is public communication. In short, public communication can be interpreted as a strategic interaction to channel information, ideas, programs, presentations, data, propaganda, and many other contexts of development messages to the masses, the public, or a specific audience. This research uses a qualitative approach with a literature study to collect data. This study found that the experience of developing a geopark tourist area in Pangandaran, West Java, can be used as the first best practice as its articulation of local wisdom in public communication during the development process showed a significant effect. In this study also shows various phenomena of successful communication integration based on local wisdom and the development process in the economic field using social media, such as the Government of Kutai Kartanegara Regency, Purwakarta Regency, Sumenep Regency. It can be concluded that the use of local wisdom-based public communication is considered capable of supporting development in terms of economic, social, or cultural